Experimentally evolved and phenotypically plastic responses to enforced monogamy in a hermaphroditic flatworm. (21st June 2016) - Janicke, T.; Sandner, P.; Ramm, S. A.; Vizoso, D. B.; Schärer, L.
Abstract: Sexual selection is considered a potent evolutionary force in all sexually reproducing organisms, but direct tests in terms of experimental evolution of sexual traits are still lacking for simultaneously hermaphroditic animals. Here, we tested how evolution under enforced monogamy affected a suite of reproductive traits (including testis area, sex allocation, genital morphology, sperm morphology and mating behaviour) in the outcrossing hermaphroditic flatworm Macrostomum lignano, using an assay that also allowed the assessment of phenotypically plastic responses to group size. The experiment comprised 32 independent selection lines that evolved under either monogamy or polygamy for 20 generations. While we did not observe an evolutionary shift in sex allocation, we detected effects of the selection regime for two male morphological traits. Specifically, worms evolving under enforced monogamy had a distinct shape of the male copulatory organ and produced sperm with shorter appendages. Many traits that did not evolve under enforced monogamy showed phenotypic plasticity in response to group size. Notably, individuals that grew up in larger groups had a more male‐biased sex allocation and produced slightly longer sperm than individuals raised in pairs. We conclude that, in this flatworm, enforced monogamy induced moderate evolutionary but substantial phenotypically plastic responses.